Pendampingan Anak-Anak TK Dharma Wanita Karangpatihan untuk Meningkatkan Kemampuan Berbicara Melalui Metode Bercerita Dengan Boneka Tangan - Dona Arynta; Ibnu Muchlis (Social Science Academic, 2023)
The problem in this research is the inaccurate increase in language skills that occurs in schools, such as: children don't want to say hello when they meet the teacher. The purpose of this research is to make it easier for children to improve their speaking skills through the storytelling method using hand puppets. This study used a qualitative method using triangulation of data, with the research subjects being group B children at TK Dharma Wanita Karangpatihan. The result of this study is the cultivation of moral values which is carried out through storytelling activities with hand puppets, namely children's insights broaden, children can be motivated and able to distinguish between good and bad, and are able to tell the contents contained in fairy tales, so that the child's behavior after listening to children's stories becomes a response to speak.